2022
DOI: 10.3390/biom12030406
|View full text |Cite
|
Sign up to set email alerts
|

Sulphoraphane Affinity-Based Chromatography for the Purification of Myrosinase from Lepidium sativum Seeds

Abstract: Sulforaphane and other natural isothiocyanates released from the respective plant glucosinolates by the plant enzyme myrosinase (β-thioglucoside glucohydrolase) show extensive anticancer and antimicrobial effects. In this study, myrosinase from garden cress (Lepidium sativum) seeds was purified to electrophoretic homogeneity by a fast and easy strategy consisting of fractionation by isoelectric precipitation with ammonium sulphate (AS) and affinity chromatography using sulforaphane (SFN) attached to cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The catalytic ability of crude Myr preparation to decompose GRN and form SFN was confirmed by an RP-HPLC analysis. We observed almost a 100% conversion of GRN to SFN under the used experimental conditions (Figure 3) at a reaction rate comparable to that measured with a purified enzyme [63,89,90]. Based on this observation, it can be concluded that the isolated GRN and the crude Myr preparation represent a suitable GLS-Myr system for the generation of SFN in biological samples under in situ conditions.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The catalytic ability of crude Myr preparation to decompose GRN and form SFN was confirmed by an RP-HPLC analysis. We observed almost a 100% conversion of GRN to SFN under the used experimental conditions (Figure 3) at a reaction rate comparable to that measured with a purified enzyme [63,89,90]. Based on this observation, it can be concluded that the isolated GRN and the crude Myr preparation represent a suitable GLS-Myr system for the generation of SFN in biological samples under in situ conditions.…”
Section: Discussionsupporting
confidence: 79%
“…The essential task was to find out if an appropriate amount of free SFN is generated during the enzymatic cleavage of GRN, which could exhibit any biological effects. We subjected the isolated GRN to enzyme hydrolysis with a crude Myr preparation obtained from swollen garden cress seeds by isoelectric precipitation with ammonium sulfate [63]. Although Myr preparation is not an electrophoretically homogeneous enzyme, it has a few advantages against purified enzymes [63], such as easy and fast preparation with a high yield and better storage stability at 4 • C (Figure S5, Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations